2021
DOI: 10.1101/2021.03.26.437123
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Occurrence of COVID-19 symptoms during SARS-CoV-2 infection defines waning of humoral immunity

Abstract: Approximately half of the SARS-CoV-2 infections occur without apparent symptoms, raising questions regarding long-term humoral immunity in asymptomatic individuals. Plasma levels of immunoglobulin G (IgG) and M (IgM) against the viral spike or nucleoprotein were determined for 25,091 individuals enrolled in a surveillance program in Wuhan, China. We compared 405 asymptomatic individuals with 459 symptomatic COVID-19 patients. The well-defined duration of the SARS-CoV-2 endemic in Wuhan allowed a side-by-side c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Obviously, this discrimination is particularly relevant during pre-symptomatic phases of infection and in the case of asymptomatic courses when symptoms cannot be used as a reference. The latter is in fact also important given that a considerable fraction of people acquire a SARS-CoV-2 infection without experiencing symptoms (Buitrago-Garcia et al, 2020;Wu et al, 2021). Additionally, modeling studies suggest that approximately half of all infections originate from individuals without symptoms (Johansson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, this discrimination is particularly relevant during pre-symptomatic phases of infection and in the case of asymptomatic courses when symptoms cannot be used as a reference. The latter is in fact also important given that a considerable fraction of people acquire a SARS-CoV-2 infection without experiencing symptoms (Buitrago-Garcia et al, 2020;Wu et al, 2021). Additionally, modeling studies suggest that approximately half of all infections originate from individuals without symptoms (Johansson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of IgM positivity peaks by week 5 and then usually becomes undetectable by week 13. SARS-CoV-2-specific IgG peaks at week 4 and stabilizes at intermediate levels during a six-month observation period after a contraction phase between week 6 and 14 (Wu et al, 2020, Wu et al, 2021. Several studies showed that specific IgG antibodies are present in the blood or sera of persons who had been infected with SARS-CoV-2 (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is more frequent in patients with preexisting conditions such as compromised immunity, and the elderly [ 2 ]. SARS-CoV-2 infections do not necessarily cause COVID-19 and a relevant fraction (in some studies up to almost half of all infections) occur without symptoms [ 3 , 4 ]. Despite the recent development of highly effective vaccines, the understanding of sustained SARS-CoV-2 immunity in the convalescent unvaccinated population remains crucial for future decision making regarding the ongoing pandemic [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Which post-entry mechanisms prevent productive SARS-CoV-2 replication in HCAECs? Does the S protein present in HCAEC result in immune responses mediated by described S-specific lymphocytes [ 6 , 11 , 21 ] or antibodies [ 24 26 ]?…”
mentioning
confidence: 99%